Surface quality improvement in meso-scale milling with spindle axial directional ultrasonic vibration assistance - Ko, Jeong Hoon. (2013)
So far, the industrial application of ultrasonic vibration assistance has been successful in continuous machining process such as turning process where ultrasonic vibration velocity is much higher than cutting velocity. Recently, vibration assistance has been experimentally investigated to the intermittent milling process mainly for feed and cross- feed directions. This paper focuses on the effect of ultrasonic vibration assistance in spindle axial direction for improvement of machined surface. With the designed ultrasonic vibration assisted milling process with 39.7 kHz and a few micro-meter amplitudes, workpiece vibrates along spindle axial direction while different RPMs and feed rates are applied. The axial directional vibration assistance acts as additional cutting motion which further reduces the leftover surface error. Experimental results validate that surface roughness can be improved from 20 % to 65 % for the tested conditions. Apparently chatter marks of the milling process are reduced with the help of the axial ultrasonic vibration assistance.